Transcendental Humanist Character Paradigm: The Reactualization of Qur'anic Values Education in Islamic Education - Viqqi Razaqtana; Abd Jalil; Dwi Mariyono (Universitas Pendidikan Ganesha, 2025)
Pedagogical practice is often trapped in a dichotomy between secular models that emphasize psychological and sociological aspects without a transcendent horizon and doctrinal models that demand normative obedience without honoring the humanity of learners. It is therefore necessary to reconsider a character education model that can integrate humanization and divine orientation, one of which is the humanist-transcendental paradigm proposed in this article. This study aims to: (1) explore the concept of the humanist-transcendental paradigm, (2) analyze Qur’anic values as its ethical and spiritual foundation, and (3) describe its implications for character formation in Islamic education. The method employed is library research. The findings indicate that, first, the humanist-transcendental paradigm conceptually combines the recognition of learners as dignified subjects with the linking of learning freedom to tawhid, adab, trustworthiness, ihsan, and God-consciousness through the teacher’s dual role as facilitator and role model. Second, Qur’anic values such as tawhid, truthfulness, trustworthiness, justice, and compassion function as living ethics that structure motivation, self-evaluation, and moral habitus toward the profile of the insan kamil. Third, this paradigm requires an integrative educational ecosystem encompassing curriculum, dialogical and ethical classroom culture, adab-based affective assessment, and the involvement of family and community in character development. The main novelty of this study lies in formulating Spiritual-Moral Self-Regulation (RDSM) as a conceptual hinge that connects the humanist and transcendental dimensions in the formation of students’ character.